Compressive behaviour of hardwood dowel reinforced CLT loaded perpendicular-to-Grain. (4th October 2021) - Moerman, Ben; Li, Minghao; Cao, Yawei; Lim, Hyungsuk
Highlights: Cross-laminated timber was reinforced perpendicular to grain with hardwood dowels. Compression tests demonstrated greater strength and stiffness with reinforcement. 3D ABAQUS models evaluated cross-laminated timber stiffness and stress distribution. Simple equation predicted compression strength of the dowel reinforced elements. Abstract: Cross-laminated timber (CLT) elements in structures may be exposed to high perpendicular-to-grain compressive stresses, which often require reinforcement to improve the inherently low strength and stiffness of timber perpendicular-to-grain. This experimental study evaluates the compressive behaviour of CLT perpendicular-to-grain when reinforced by hardwood dowels. Groups of 3 and 5-ply CLT specimens with dimensions of 400 mm × 400 mm, with and without dowel reinforcement, were tested. The specimen with the most reinforcement, 5-ply Douglas Fir CLT reinforced with 4-ф25mm American White Ash dowels, achieved a mean strength and stiffness increase of 120% and 240%, respectively. Finite element models were created in ABAQUS to predict the stiffness of tested CLT specimens and to evaluate the distribution of compressive stresses. Finally, a simple design equation is presented and provides reasonable strength predictions for the reinforced CLT.